CHANGER DATA APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Indirmawan Indirmawan; Yulina, SKom, MMSI Yulina, SKom, MMSI (Jurnal Sistem Informasi, 2004)
With the development and advancement of information technology is increasinglysophisticated computer plays an important role in it, let alone a computer equippedwith facilities and infrastructure are growing rapidly.In its activities the computer user can not be separated from the data. The data itselfhas several types of data. To perform the data transfer then we should do first datatype modifiers. In performing data type conversions, many computer users still do notknow the lay and how way of doing data type conversions. With this application, thedata type modifiers can help our customers in terms of computer transfers the datawhich will optimize the time available.